Bone marrow mesenchymal stem cell-derived exosomal miR-30e-5p ameliorates high-glucose induced renal proximal tubular cell pyroptosis by inhibiting ELAVL1 - Lv, Jia; Hao, Ya-Ning; Wang, Xiao-Pei; Lu, Wan-Hong; Xie, Li-Yi; Niu, Dan (Renal failure, 2023)
The rapid increase in the prevalence of diabetes has resulted in more cases of diabetic kidney disease (DKD). Treatment with bone marrow mesenchymal stem cells (BMSCs) may represent an alternative strategy to manage DKD. HK-2 cells were treated with 30 mM high glucose (HG). Bone marrow MSC-derived exosomes (BMSC-exos) were isolated and internalized into HK-2 cells. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide (MTT) and lactate dehydrogenase (LDH) assays were used to measure viability and cytotoxicity. The secretion of IL-1β and IL-18 was measured by ELISA. Pyroptosis was assessed by flow cytometry. Quantitative RT-PCR was used to measure the levels of miR-30e-5p, ELAV like RNA binding protein 1 (ELAVL1), IL-1β, and IL-18. The expression of ELAVL1 and pyroptosis-associated cytokine proteins was determined by western blot analysis. A dual-luciferase reporter gene assay was conducted to confirm the relationship between miR-30e-5p and ELAVL1. BMSC-exos decreased LDH, IL-1β, and IL-18 secretion and inhibited the expression of the pyroptosis-related factors (IL-1β, caspase-1, GSDMD-N, and NLRP3) in HG-induced HK-2 cells. Moreover, miR-30e-5p depletion derived from BMSC-exos promoted HK-2 cell pyroptosis. Besides, miR-30e-5p over-expression or ELVAL1 knockdown could directly inhibit pyroptosis. ELAVL1 was a target of miR-30e-5p and knocking down ELAVL1 reversed the effect of miR-30e-5p inhibition in BMSC-exos-treated HK-2 cells. BMSC-derived exosomal miR-30e-5p inhibits caspase-1-mediated pyroptosis by targeting ELAVL1 in HG-induced HK-2 cells, which might provide a new strategy for treating DKD.